(untitled) (International Journal of Natural Sciences, 2011)
Environmental as well as genotypic effect on weight gain is a normal phenomenon. The aim of the present study was to determine the environment and breed effect on weight gain. One observational cross-sectional study was done on the Fayoumi and Sonali chicks at Chittagong and Noakhali district from October 2005 to July 2006. A total of 48 farmers (24 from each Upazila) were selected randomly, who rear chicks under scavenging condition as well as had broody hens. Twelve eggs of each breed were supplied to each farmer. The chicks were hatched out by the farmers managed broody hens. Then the chicks were reared under scavenging system. The weight-gain of Fayoumi chicks after 8 weeks was higher (226.0 gm) than Sonali (170.7 gm) and it differed significantly (χ2 = 7.71, df = 1, p < 0.01). The Fayoumi chicks of Chittagong site gained higher weight (285.4 gm) than that of Noakhali (171.1 gm). In case of Sonali chicks, the weight gain of day old to eight weeks aged showed the similar performance in both Districts. Chicks of both breeds gained better weight in Chittagong than Noakhali significantly (Fayoumi: χ2 = 28.6, df = 1, p < 0.001; Sonali: χ2 = 10.01, df = 1, p < 0.01). Weight gain and environmental adaptation of Fayoumi chicks were better than Sonali. Key words: Environment; Fayoumi; genotype; Sonali; weight gain. DOI: http://dx.doi.org/10.3329/ijns.v1i1.8611 International Journal of Natural Sciences (2011), 1(1):22-24